Relative Performance Feedback and Long-Term Tasks – Experimental Evidence from Higher Education - Raphael Brade; Oliver Himmler; Robert Jaeckle (Center for Economic Studies and ifo Institute (CESifo), 2023)
We present first experimental evidence that relative performance feedback improves both the speed and quality with which challenging long-term tasks are completed. Providing university students with ongoing relative feedback on accumulated course credits accelerates graduation by 0.12 SD, and also improves grades by 0.063 SD. Treatment effects are concentrated among students with medium pre-treatment graduation probabilities: when these students are informed about an above-average performance, their outcomes improve – otherwise their outcomes deteriorate. Combined with survey evidence, this pattern of results suggests that learning about own ability is a plausible mechanism.
Keywords: C93; D83; D91; I21; I23; I24; 330; relative performance feedback; rank; natural field experiment; higher education; perceived ability; belief updating